Dosis Npk Dan Konsentrasi Zat Pengatur Tumbuh Tidak Mempengaruhi Pertumbuhan Tanaman Sawi (Brassica Juncea L.) - Muhammad Muaz Munauwar; Sri Jaya (Agrium, 2018)
The purpose of this research is to observe the dosage of natrium, phospor and kalium fertilizer and the concentration of Atonic Growth Regulators appropriate for the growth and production of mustard greens (Brassica juncea, L) is good, and interaction of both factors. This research was conducted in Batumbulan Asli Village, Babussalam Sub-district, Southeast Aceh Regency with its height ± 220 m above sea. This research done in December 2016-January 2017, using Random Block Design (RBD) Factorial, which consists of 2 (two) factors. The first factor is the dosage of fertilizer (N) consisting of 3 levels, N1 = 0.50 gr /plot, N2 = 1 gr/ plot and N3 = 1.5 gr / plot. The second factor is the concentration of Atonic Growth Atonic Growth Regulator (A) consisting of 3 levels, A1 = 0.50 cc / l water, A2 = 1 cc /l water and A3 = 1.5 cc /l water. Parameters observed were plant height, number of leaves and leaf area. The results reported that fertilizers did not significantly affect the growth, but there was a tendency where the fertilizers and growth regulator fertilizer could increase the growth of mustard plant